Premature mortality of epilepsy in low- and middle-income countries: A systematic review from the Mortality Task Force of the International League Against Epilepsy. - Levira, F; Thurman, D; Sander, J; Hauser, W; Hesdorffer, D; Masanja, H; Odermatt, P; Logroscino, G; Newton, C; Epilepsy, E (Wiley, 2016)
Objectives To determine the magnitude, risk factors and causes of premature mortality associated with epilepsy in low and middle income countries (LMIC). Methods We conducted a systematic search of the literature reporting mortality and epilepsy in the World Bank-defined LMIC. We assessed the quality of the studies based upon representativeness, ascertainment of cases, diagnosis, and mortality, and extracted data on standardized mortality ratios (SMR) and mortality rates in people with epilepsy. We examined risk factors and causes of death. Results The annual mortality rate was estimated at 19.8 (range 9.7-45.1) deaths per 1000 people with epilepsy with a weighted median SMR of 2.6 (range 1.3-7.2) among higher-quality population-based studies. Clinical cohort studies yielded 7.1 (range 1.6-25.1) deaths per 1000 people. The weighted median SMRs were 5.0 in males and 4.5 in females; relatively higher SMRs within studies were measured among children and adolescents, those with symptomatic epilepsies, and those reporting less adherence to treatment. The main causes of death in people with epilepsy living in LMICs include those directly attributable to epilepsy, which yield a mean proportional mortality ratio (PMR) of 27.3% (range 5%-75.5%) derived from population-based studies. These direct causes comprise status epilepticus, with reported PMRs ranging from 5%-56.6%, and sudden unexpected death in epilepsy, with reported PMRs ranging from 1%-18.9%. Important causes of mortality indirectly related to epilepsy include drowning, head injury, and burns. Significance Epilepsy in LMIC has a significantly greater premature mortality, as in high-income countries, but in LMIC the excess mortality is more likely to be associated with causes attributable to lack of access to medical facilities such as status epilepticus, and preventable causes such as drowning, head injuries and burns. This excess premature mortality could be substantially reduced with education about the risk of death and improved access to treatments, including AEDs.